Research on Silver Tourism in China: Themes, Theoretical Frameworks, and Methodological Approaches - Yao, Wenxuan; He, Biao (Asia Pacific Economic and Management Review, 2025)
The silver economy, driven by the rapid aging of China’s population, has emerged as a significant frontier for both academic research and market development. With over a thousand scholarly works dedicated to elderly tourism, this review consolidates the core knowledge base of "silver tourism," integrating studies from the fields of senior and elderly travel. It systematically examines three primary dimensions: the preferences and behavioural characteristics of senior tourists; the development and differentiation of tourism products tailored to this demographic; and the segmentation of regional and subgroup markets. Moreover, it outlines the dominant theoretical frameworks and interdisciplinary methodologies adopted by scholars, drawing upon over three decades of literature (1993–2025). In light of recent policy initiatives and technological transformations, this paper aims to provide a comprehensive and critical foundation for future academic exploration and practical innovation.